A new specimen for high-grade pipeline steels CTOA test. (November 2015) - Di, Yan; Shuai, Jian; Wang, Junqiang; Tu, Shengwen
Highlights: Modified compact tension specimen (MCT) was designed for CTOA measurement. MCT specimen alleviates the weakness of MDCB specimen for pipeline steel CTOA test. DIC technology and FEA method were adopted to verify the accuracy of test results. Results show that MCT specimen is available for CTOA measure. Abstract: In order to accurately measure CTOA of high-grade pipeline steels, a new modified compact tension (MCT) specimen was designed to alleviate the drawbacks of standard tests specimens and MDCB specimen. CTOA of X80 pipeline steel was measured using DIC technology with MCT specimen which behaves steady-state propagation in tearing process. FE method was adopted to verify the accuracy of results acquired from experiment tests. Results from DIC technology agree well with those from FE method. Based on the results of tests, FE simulation and comparison with MDCB specimen test previously conducted with the same material, it shows that MCT specimen is available for high grade pipeline steel CTOA test.